ما قبل الضروري في السياسة عند ابن رشد " دراسة تحليلية للأفكار السياسية الرشدية في كتاب تلخيص الخطابة " - الضاهر, سليمان; صارم, علي (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يُعنى هذا البحث بالوقوف على أهم الأفكار السياسية التي تناولها ابن رشد من خلال تلخيصه لكتاب الخطابة الأرسطي، وذلك خلافا لابن سينا والفارابي اللذين نظرا إلى الكتاب من وجهة نظر منطقية. بيد أننا لن ننشغل بالأفكار المنطقية الواردة في كتاب الخطابة بقدر ما سنحاول التركيز على مسائل الفلسفة السياسية الأرسطية التي اعتمدها ابن رشد في تلخيصه لكتاب الخطابة؛ أي محاولة التركيز على الأفكار السياسية الرشدية التي سبقت تلخيصه لجمهورية أفلاطون بدعوى عدم حصوله على ترجمة عربية لكتاب " السياسة " الأرسطي. نحاول في هذا البحث الوقوف على الأسلوب الذي اتبعه ابن رشد في التلخيص، لجهة التقيد بالنص الأرسطي ودلالته الحرفية في بعض الأحيان، أو القراءة التأويلية في أحيان أُخرَ، ولجهة إضافة بعض التعليقات والاستطرادات على العبارة الأرسطية في ناحية ثانية. واعتماده أيضا على شروح سابقيه للكتاب نفسه في توضيح بعض العبارات، ومن ثم محاولة تطبيق الأفكار السياسية الأرسطية على الواقع السياسي العربي الإسلامي في العصر الوسيط. This research deals with the most important political ideas that Averroes dealt with through his summarization of the Aristotle's book Rhetoric, in contrast to Avicenna and Al-Farabi's logical approach to this book. We will not go through the logical ideas in Rhetoric but rather focus on the Aristotelian political and philosophical issues which Averroes depends on in his summary of the book. It is an attempt to focus on Averroes's political ideas which preceded his summarization of Plato 's The Republic due to the fact that he didn't obtain the Arabic translation of Aristotle's book Politics. We try in this research to focus on Averroes's way of summary regarding commitment to the Aristotelian text and its literal denotations on some occasions, or the interpretive reading on other occasions. In addition, it will focus on Averroes's reliance on his predecessors' explanations of the same book to clarify some statements, and then his attempt to apply some Aristotelian political ideas on the Arab-Muslim political reality in the Middle Ages.